Systemic lupus erythromatosus presenting as cardiac tamponade: a rare and life-threatening presentation - Kothia, Darpan; Nagar, Madhvi; Nandania, Parthkumar; Chatterjee, S. S. (International Journal of Research in Medical Sciences, 2024)
We present a case of a 35-year-old female with 3-4 months history of left sided chest pain, low grade fever, dyspnea on exertion, dry cough, fatigue and myalgia. Initial investigations including pleural fluid CBNAAT was negative. Empiric anti- tuberculosis therapy was initiated based on clinical and radiological findings. Despite treatment, symptoms persisted. Subsequent evaluation including echocardiography which showed moderate pericardial effusion along with special investigations leading to a diagnosis of systemic lupus erythematosus. Treatment with corticosteroid resulted in significant symptom improvement. This case highlights the importance of considering systemic lupus erythematosus in patients with atypical presentations, even in absence of classic features.